Non-destructive pulsed field CuAg-solenoids - Freudenberger, J; Lyubimova, J; Gaganov, A; Witte, H; Hickman, A; Jones, H; Nganbe, M (2010)
Ultra strong CuAg-based conductor materials have been developed and tested in pulsed high-field magnets. The yield strength of a cold deformed CuAgZr conductor material has been assessed on the basis of different hardening mechanisms: solid solution, grain boundary, precipitation and dislocation hardening. The experimental value for the yield strength when transferred to the shear strength by Schmid's law is between a linear and a quadratic superposition of the individual critical shear stresses and hence found to be in good agreement with the theoretical predictions. The conductor material shows an ultimate tensile strength of more than 1.1 GPa at room temperature (yield strength about 1 GPa, plastic strain: 0.7%). Based on the properties of the CuAgZr material a new coil has been designed and tested. The coil features additional internal reinforcement layers, which are optimised using computer simulations. In combination with refined computer simulation techniques, such as finite element modelling, significant progress was made concerning the use of these materials for pulsed magnet applications. The coil generated a field of 66 T without being destroyed, which constitutes a new high-field record of the Clarendon Laboratory in Oxford, UK. Performance and measurements are in good agreement with simulations. © 2009 Elsevier B.V.